(untitled) (Eurasian Journal of Philology Science and Education, 2020)
This article discusses the concept of values which is widely discussed at different stages in the Kazakh society.The culture of humanity, its social behavior and thinking cannot live outside of language. The cultural characteristics of each nation are manifested in the language that has been formed over the centuries. Any social social relations are based on cultural content, including values. Within the framework of the пeneral axiology, we will consider «linguistic axiology». The correlation of axiology and linguistics will allow us to study the axiological field of language. In addition, in the system “ManLanguage-World” special attention is paid to the main values of human development and existence of society that are displayed in the language. The objective of this direction – determination of methods and technologies of exploring the inner world of linguistic identity through language data to research the relationship of individual and society to values. Lingvoaxiology in modern linguistics gives you the opportunity to explore values, to examine and research the system of values. For linguistic axiology, it is important, first of all, to consider the concept of «evaluation» in the axiological paradigm. Values are closely related to the rating category. Evaluation is a form of defining quality as a cognitive phenomenon. Evaluation is generally understood as knowing the world and experience of perception, recognition of the subject in the space of life. By evaluating, we perceive values. The assessment of human cognition, knowledge and culture is carried out depending on the general level of intelligence. Through evaluation, we conduct a linguistic axiological analysis, which reflects the axiological aspects of the linguistic picture of the world.